Application of a VARANS based resistance-type porosity model on simulating wave interactions with perforated caisson sitting on a rubble-mound foundation. (July 2021) - Zhao, Peihong; Sun, Dapeng; Wu, Hao
Abstract: Rubble-mound foundation can be regarded as a form of porous structure that is widely used in engineering practice. Porous medium flow must be considered when simulating wave interactions with perforated caisson sitting on a rubble-mound foundation. In this paper, volume-averaged/Reynolds averaged Navier-Stokes (VARANS) equations are adopted to describe the flow inside and outside the porous structure. Moreover, they are combined with the volume averaged k − ε model to simulate the turbulence effect. In addition, the three-step finite element method is applied to solve VARANS equations numerically, and the CLEAR-VOF method is applied to capture the free fluid surface. The resistance-type porosity numerical model is proposed and verified by several test cases and then used to simulate wave interactions with perforated caisson sitting on a rubble-mound foundation. The porosity model gives reliable results compared to the experiments with respect to the wave height, the pressure distribution, and the total vertical wave force. The model can be adopted to study the wave interaction with perforated caisson sitting on a rubble-mound foundation and used for the design of such caisson in engineering practice.